2017
DOI: 10.1111/dom.12900
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise combined with glucagon‐like peptide‐1 receptor agonist treatment on cardiac function: A randomized double‐blind placebo‐controlled clinical trial

Abstract: In patients with type 2 diabetes, both supervised exercise and treatment with the glucagon-like peptide-1 (GLP-1) receptor agonist (GLP-1RA) liraglutide may improve cardiac function. We evaluated cardiac function before and after 16 weeks of treatment with the GLP-1RA liraglutide or placebo, combined with supervised exercise, in 33 dysregulated patients with type 2 diabetes on diet and/or metformin. Early diastolic myocardial tissue velocity was improved by exercise in the placebo group (mean AE standard devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 19 publications
2
33
0
Order By: Relevance
“…Recent large well-conducted randomized studies have demonstrated neutral effect with GLP-1RA on stabile heart failure ( 7 ), or advanced heart failure ( 34 ), in patients with and without diabetes. Among patients hospitalized with heart failure, liraglutide treatment did not lead to greater clinical stability ( 6 ), a finding concordant with some other small clinical studies showing no beneficial effects from GLP-1RA on heart failure ( 8 , 35 ). A recent double-blind placebo-controlled crossover study, which used dobutamine stress TDE, to investigate changes in systolic heart function in newly diagnosed T2D patients with coronary artery disease, also failed to show any beneficial action from liraglutide treatment compared with placebo treatment ( 14 ).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Recent large well-conducted randomized studies have demonstrated neutral effect with GLP-1RA on stabile heart failure ( 7 ), or advanced heart failure ( 34 ), in patients with and without diabetes. Among patients hospitalized with heart failure, liraglutide treatment did not lead to greater clinical stability ( 6 ), a finding concordant with some other small clinical studies showing no beneficial effects from GLP-1RA on heart failure ( 8 , 35 ). A recent double-blind placebo-controlled crossover study, which used dobutamine stress TDE, to investigate changes in systolic heart function in newly diagnosed T2D patients with coronary artery disease, also failed to show any beneficial action from liraglutide treatment compared with placebo treatment ( 14 ).…”
Section: Discussionsupporting
confidence: 84%
“…Our study results contrast with a recent study where 33 T2D patients were treated with liraglutide for 16 weeks compared with placebo add on to supervised exercise. In that study, there was no change in HR between groups; however diastolic function upon supervised exercise was improved in the placebo group and blunted in the liraglutide treated T2D patients ( 8 ). In our study, we used bicycle ergometer exercise to sharp the sensitivity of our method, and not for the treatment of diastolic function, therefore studies are not easy to compare.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although incretin‐based agents reduce epicardial fat volume, glucagon‐like peptide‐1 receptor agonism promotes adverse change in the biology of adipose tissue, and dipeptidyl peptidase‐4 inhibitors can potentiate the actions of proinflammatory chemokines . Perhaps for these reasons, in the clinical setting, incretin‐based drugs have not improved ventricular diastolic filling dynamics or reduced the risk of heart failure …”
Section: Epicardial Adipose Tissues As a Therapeutic Target In Typementioning
confidence: 99%
“…Resveratrol (PubChem CID: 445154) can be found in several food sources including grapes and red wine [21]. Interestingly, experimental evidence reporting on the comparative or combination use of metformin (PubChem CID: 4091) with well-known bioactive compounds like resveratrol has become of great interest [22][23][24][25][26][27]. Although metformin is a commonly used antidiabetic drug, information on its comparative or combination use with resveratrol has not been assessed to understand the potential synergistic or combination advantages of such a therapy in managing metabolic complications.…”
Section: Introductionmentioning
confidence: 99%